IMPLEMENTASI PROGRAM KAMPUNG KB DI DESA KOTO BARU KECAMATAN KOTO BARU KOTA SUNGAI PENUH - KURNIAWAN, DWI CAHYO; Iskarni, Paus (DEPARTEMEN GEOGRAFI FIS UNP, 2024)
This research aims to: 1) understand the implementation of the Toddler Family Development Program in the village of Koto Baru. 2) Understand the implementation of the Adolescent Family Development Program in the village of Koto Baru. 3) Understand the implementation of the Elderly Family Development Program in the village of Koto Baru. 4) Understand the implementation of the Youth Information Center Program in the village of Koto Baru. 5) Identify the obstacles in the implementation of the Family Planning Village Program in the village of Koto Baru. The research method used in this study is a mixed method with quantitative and qualitative analysis techniques. The samples in this study consist of 34 toddlers participating in the Toddler Family Development Program (BKB), 41 adolescents participating in the Adolescent Family Development Program (BKR), 38 elderly people participating in the Elderly Family Development Program (BKL), 16 adolescents participating in the Youth Information Center Program (PIKR), and 13 people participating in the Youth Productive Health Information and Services Program (UPPKS). The results of this research show that the implementation of the Toddler Family Development Program involves an average of 9 attended toddlers in supplementary feeding activities, 9 attended toddlers in posyandu (integrated health post) weighing sessions, and 11 toddlers receiving vitamin supplements. For the Adolescent Family Development Program, the average attendance of adolescents in drug counseling activities is 14, 14 adolescents attended the age of marriage socialization, and 21 adolescents participated in risk behavior discussions. Regarding the Elderly Family Development Program, the average attendance of the elderly in the elderly posbindu (integrated elderly health post) activities is 13, 10 elderly people participated in elderly gymnastics, and 10 elderly people attended the taklim assembly (Islamic study group). For the Youth Information Center Program, the attendance in youth PIKR (Youth Information and Communication Center) competition activities was 10, 10 youths attended the marriage age maturity session, and 10 youths participated in the evaluation of adolescent puberty guidance. In the Youth Productive Health Information and Services Program, 7 people participated in the agricultural group coaching activity, 7 people were involved in the production of red ginger products, and 7 people engaged in capital investment for the group. The obstacles in the implementation of the Family Planning Village Program include insufficient community participation, inadequate facilities and infrastructure for program activities, and the lack of adequate equipment to support the production of beverages from red ginger.